IMPLEMENTATION OF EXPERIMENT METHOD TO INCREASE STUDY ATTITUDES AND STUDENT LEARNING ACHIEVEMENTS - Puryadi Puryadi; Bambang Sahono; Turdjai Turdjai (UNIB Press, 2017)
This study aims to describe scientific attitudes and student achievement as well as to know the effectiveness of the application of experimental method to student achievement.The method used in this research is a combination method of classroom action research and quasi experiment.The research subject is a class action fifth grade students of State Elementary School 03 Taba Penanjung year 2016/2017 2nd half totaled 22 students.The population of this quasi-experimental research is all the students of grade V of State Elementary School of Class II Taba Penanjung Bengkulu Tengah. The sample of his research was selected by two classes at the Central Elementary School 07 Taba Penanjung Bengkulu Tengah that is class VA and VB.Technique of collecting data using observation sheet and test.Data analysis uses mean and t-test. The results concluded that: (1) Application of experimental methodcan improve students' scientific attitude;(2) Application of experiment method can significantly improve student's learning achievement, and (3) Application of effective experiment method can effectively improve student's learning achievement. Keywords: experimental method, scientific attitude and achievement